The Global Drug Facility: a unique, holistic and pioneering approach to drug procurement and management - Robert Matiru; Timothy Ryan
In January 2006, the Stop TB Partnership launched the Global Plan to Stop TB 2006-2015, which describes the actions and resources needed to reduce tuberculosis (TB) incidence, prevalence and deaths. A fundamental aim of the Global Plan is to expand equitable access to affordable high-quality anti-tuberculous drugs and diagnostics. A principal tool developed by the Stop TB Partnership to achieve this is the Global Drug Facility (GDF). This paper demonstrates the GDF's unique, holistic and pioneering approach to drug procurement and management by analysing its key achievements. One of these has been to provide 9 million patient-treatments to 78 countries in its first 6 years of operation. The GDF recognized that the incentives provided by free or affordable anti-tuberculosis drugs are not sufficient to induce governments to improve their programmes' standards and coverage, nor does the provision of free or affordable drugs guarantee that there is broad access to, and use of, drug treatment in cases where procurement systems are weak, regulatory hurdles exist or there are unreliable distribution and storage systems. Thus, the paper also illustrates how the GDF has contributed towards making sustained improvements in the capacity of countries worldwide to properly manage their anti-TB drugs. This paper also assesses some of the limitations, shortcomings and risks associated with the model. The paper concludes by examining the GDF's key plans and strategies for the future, and the challenges associated with implementation.